Historiography of Dr. Tabassum Kashmiri and New Concepts of Literary History - Khadim Hussain (بازیافت, 2019)
Dr.Tabassum Kashmiri is renowned a scholar of Urdu literature. He is a poet, critic, researcher and literary historian. This article gives a meticulous analysis of Literary History of Urdu Literature written by him in the light of basic and vital principles of literary history and historiography. In this article we also discussed the multidimensional aspect of his history in the light of his vision, modern critical approach and his distinctive style. How and where this multidisciplinary study works? An attempt has been made to measure and encompass the depth and breadth of his literary history. This article also spotlights some singificant features of his writing.